Price Analysis Practices in the Pig Sector - Marczin, Tamás (International Journal of Engineering and Management Sciences, 2024)
The analysis of sales prices has become a particularly important topic in pig production research, including statistical analysis. With globalisation, we can say that today we are talking about a sector constantly exposed to the effects of the world market. It is also worth pointing out that, compared with other sectors, the impact of external regulation and influence is less pronounced. Thus, the aim of the present research was to identify the journal articles published on the subject of price analysis and, on the basis of these, to establish the correlation with the methodologies often used. It examines the spatial location of price analysis. The results obtained show that the practice of price analysis is mainly carried out in the context of market leading countries, usually on the basis of a cross product chain issue. The research shows the emergence in recent years of increasingly sophisticated methodologies that allow more accurate conclusions to be drawn, while also facilitating planning from a practical point of view.